The Fake News in the Digital Environment: From the Information Pandemic to Packaged Awareness in the Context of the Russian-Ukrainian War - Allal, Abdelkader (Journal of Ecohumanism, 2026)
Technological development has created a fertile space for circulating, exchanging, and disseminating information on the widest possible scale, embodying the essence of interactivity in its clearest manifestations. At the same time, it has opened the way for exploiting this openness and fluidity in employing such news for purposes ranging from ideological and psychological manipulation to disrupting audience choices and positions, as well as shaping public opinion. This pattern of "mechanizing" news may begin with a professional error, move through the fabrication of falsehoods and the falsification of information, and eventually lead to the formation of "packaged" awareness and the manipulation of minds. This is what we address through epistemic interpretation and in-depth analysis in this research paper within the context of the Russian-Ukrainian war.